Effects of Amyloid Precursor Protein 17 Peptide on the Protection of Diabetic Encephalopathy and Improvement of Glycol Metabolism in the Diabetic Rat - Heng Meng; Duo Zhang; Haishan Yang (Journal of Diabetes Research)
Researchers have proposed that amyloid precursor protein 17 peptide (APP17 peptide), an active fragment of amyloid precursor protein (APP) in the nervous system, has therapeutic effects on neurodegeneration. Diabetic encephalopathy (DE) is a neurological disease caused by diabetes. Here we use multiple experimental approaches to investigate the effect of APP17 peptide on changes in learning behavior and glycol metabolism in rats. It was found that rats with DE treated by APP17 peptide showed reversed behavioral alternation. The [18F]-FDG-PET images and other results all showed that the APP17 peptide could promote glucose metabolism in the brain of the DE rat model. Meanwhile, the insulin signaling was markedly increased as shown by increased phosphorylation of Akt and enhanced GLUT4 activation. Compared with the DE group, the activities of SOD, GSH-Px, and CAT in the rat hippocampal gyrus were increased, while MDA decreased markedly in the DE + APP17 peptide group. No amyloid plaques in the cortex and the hippocampus were detected in either group, indicating that the experimental animals in the current study were not suffering from Alzheimer’s disease. These results indicate that APP17 peptide could be used to treat DE effectively.